Study of nuclear energy as an alternative energy source in satellites applying the SPDC effect - et. al., Fredys A. Simanca H., (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this study is to look for an alternative in the collection of energy in satellites without the inefficient conversion of solar energy and, since in the area of umbra or eclipse, when it does not receive direct solar radiation, problems may arise because it does not have enough energy supply to function, so, nuclear energy is considered as an alternative energy source applying the SPDC effect (spontaneous parametric descending conversion), waiting for the satellite to supply energy anywhere it is located. Similarly, it was determined that by using nuclear material as an energy source, it not only improves but also optimizes energy supply in space missions with CubeSat nanosatellites. Based on the results of the study, it is concluded that not only would the supply of satellites be optimized, but also would lead to savings in the cost of producing them.